Harmonic circulation and DC voltage instability mechanism of parallel‐SVG system. Issue 5 (21st February 2020) - Chen, Jikai; Shao, Hui; Cheng, Yiping; Wang, Xiaozhe; Li, Guoqing; Sun, Chu; Jiang, Qirong; Qin, Jiangchao
Abstract : A parallel static var generator (SVG) system based on cascaded H‐bridge topology in wind afflux station is analysed in this study to reveal the mechanism of harmonic current and DC voltage instability due to the phase difference between the PWM carriers. First, the inherent relation of harmonic current and low‐frequency disturbance is revealed by carrier‐phase‐shift pulse‐width‐modulation (CPS‐PWM) theory. Second, to identify the negative impact of low‐frequency disturbance, a small‐signal circuit model is built to research the electric coupling relation between SVGs and the grid, then pointing out the main factors which affect the harmonic circulation among the two‐paralleled SVGs. Third, the output impedance and the transfer function of SVG give an insight into the interaction between SVG and low‐frequency resonance characteristics, based on which a virtual resistance method is proposed to shape the resonant peak. Finally, theoretical analysis and system experiment prove that the proposed control strategy can rapidly attenuate low‐frequency resonant peaks of the system, avoiding the DC voltage instability in the SVG system when harmonic circulation occurs.